Prediction and causes of open gingival embrasure spaces between the mandibular central incisors following orthodontic treatment - Ikeda Tadataka; Yamaguchi Masaru; Meguro Daijiro; Kasai Kazutaka (Sciendo, 2004)
Background: An open gingival embrasure space (OGES) between the mandibular incisors, also known as a "black triangle" (BT), can be an undesirable outcome of adult orthodontic treatment.